2017
DOI: 10.1111/ecc.12724
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotherapy in bone metastases: A critical review of current literature

Abstract: Radiotherapy is considered the treatment of choice for painful bone metastases. However, novel modalities of radiotherapy have emerged in the concept of oligometastasic disease. In addition, the increase of overall survival of patients with bone metastatic disease in the last decades due to systemic treatments has issued the silent topic of re-irradiation. The aim of this manuscript was to present a current thorough search of relevant literature. Originally, 6,087 articles revealed from PubMed database related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 107 publications
0
17
0
1
Order By: Relevance
“…For patients with painful bone metastases, QOL is the main health-related factor that is affected 24. According to the comparison of QOL scores (including quality of sleep, appetite, mental state, and fatigue), there was a significant difference between 125 I brachytherapy and EBRT at T 2 and T 4 ( P <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with painful bone metastases, QOL is the main health-related factor that is affected 24. According to the comparison of QOL scores (including quality of sleep, appetite, mental state, and fatigue), there was a significant difference between 125 I brachytherapy and EBRT at T 2 and T 4 ( P <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment modality of choice for palliation of metastatic bone metastases is considered to be local site radiotherapy [10]. There are various fractionation schedules of radiotherapy used for the palliation of bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies conducted worldwide have shown single session radiotherapy to be equally effective as multifraction radiotherapy in palliation of bone metastases [11-13]. A recent meta-analysis to find the role of radiotherapy in bone metastases have shown no statistically difference in complete response or overall response to radiotherapy among various fractionations but found higher retreatment rates in the single fraction arms [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is used to treat approximately 80% of patients with head and neck cancer and undeniably achieves favorable disease control in the great majority of head and neck patients [2]. For other types of cancer, radiotherapy also has a clear benefit for both long-term survival and local recurrence rate [3][4][5].…”
Section: Introductionmentioning
confidence: 99%